Oxidative Stress, Inflammation, Gut Dysbiosis: What Can Polyphenols Do in Inflammatory Bowel Disease? - Lei Li; Peilan Peng; Ning Ding; Wenhui Jia; Canhua Huang; Yong Tang (MDPI AG, 2023)
Inflammatory bowel disease (IBD) is a long-term, progressive, and recurrent intestinal inflammatory disorder. The pathogenic mechanisms of IBD are multifaceted and associated with oxidative stress, unbalanced gut microbiota, and aberrant immune response. Indeed, oxidative stress can affect the progression and development of IBD by regulating the homeostasis of the gut microbiota and immune response. Therefore, redox-targeted therapy is a promising treatment option for IBD. Recent evidence has verified that Chinese herbal medicine (CHM)-derived polyphenols, natural antioxidants, are able to maintain redox equilibrium in the intestinal tract to prevent abnormal gut microbiota and radical inflammatory responses. Here, we provide a comprehensive perspective for implementing natural antioxidants as potential IBD candidate medications. In addition, we demonstrate novel technologies and stratagems for promoting the antioxidative properties of CHM-derived polyphenols, including novel delivery systems, chemical modifications, and combination strategies.